Characterization of electron beams emitted from dense plasma focus machines using argon, neon and nitrogen - Akel, Mohamad; Al-Hawat, Sh.; Lee, Sing; Saw, Sor Heoh (World Scientific Publishing, 2018)
The measured current traces of two low energy machines namely the AECS PF-2 and INTI PF are used for studying of the produced electron beam features using the modified Lee code (RADPFV5.15REB) at different conditions. The fitting procedures between measured and computed current traces are made for each point of pressure. In the case of AECS PF-2 working with neon, the electron fluence reaches the maximum value 2.35 × 1022 electrons m-2 for 1.6 Torr and the flux achieves 2.42 × 1030 electrons m-2s-1 near 1.5 Torr. The electron number has a peak of 5.74 × 1014 at 0.9 Torr. The computed results demonstarte also the maximum value of the power flow density of 2.44 × 1016 Wm-2, and the superior damage factor of around 1.95 × 1012 Wm-2s0.5 at a pressure of 0.4 Torr. Argon presents the action of radiative cooling topping at highly magnified 6.13 × 1031 m-2s-1 at 0.9 Torr. The damage factor reaches almost 175 × 1012 Wm-2s0.5 for Ar but it is only 1.29 × 1012 Wm-2s0.5 for N2. The huge values for argon are a result of enhanced compression due to radiative cooling. In the case of INTI PF device, the electron energy extends from 58 keV (for N2) to 256 keV (for Ar). The results indicate that the electron fluence ranges from 2 × 1022 electrons m-2 for N2 to 88 × 1022 electrons m-2 for Ar.